Home Based Care (HBC) providers knowledge attitude and perception of identification treatment and referrals of common symptoms of Acquired Immune Deficiency Syndrome (AIDS) in Botswana - Akhiwu, Patrick (Department of Public Health and Family Medicine, 2016)
Home based care is a major intervention in the management of HIV/AIDS and other illnesses in need of palliative care, especially in situations where resources are limited. The challenges associated with HIV/AIDS infection in Botswana resulted in the training of home based care volunteers (HBCV) to assist in the fight against HIV/AIDS. The HBCV regularly visit and assist ill patients at home. They provided support with home activities and basic health care. They are to note changes in their clients' condition, and, if necessary, report to the home based team at the clinics f or further action. The purpose of this study was to explore their knowledge, attitude, and perception in the identification, management, and referral of common symptoms of HIV/AIDS. METHODOLOGY: A cross sectional study of thirty three HBCV participants using a semi - structured interview guide was carried out. Closed and open ended questions were used to collect sociodemographic data and explore their knowledge, attitudes, and perception in relation to the identification, management, and referral of common symptoms of HIV /AIDS. A 5 point Likert scale was used to access their confidence with caring for different symptoms. The response to the open - minded ended question were coded and analysed qualitatively using thematic analysis. RESULTS AND CONCLUSION: Most of the participants were women. The study revealed that fatigue, weakness and pain were the symptoms most identified by HBCV. Other symptoms like diarrhoea were also identified with HBCV demonstrating satisfactory basic knowledge and management of these symptoms. They were aware of common symptoms of opportunistic diseases like tuberculosis and the need to refer such patients. Majority of HBCV were "comfortable" or "very comfortable" with their role of referring patients for symptom management. This study exposed the negative experiences of HBCV, which included stress, fatigue, helplessness, dealing with difficult families, fear of HIV infection, and death of clients. It also highlighted their positive experiences of community appreciation, financial reward, providing symptom relief, spiritual development, increased knowledge, and having a sense of "Botho" (humanness and community responsibility). This study showed the knowledge of the HBCV in relation to HIV/AIDS and associated symptoms. It also presented their attitude and perceptions with the management and referral of these symptoms.